2009 Conference Record of the Forty-Third Asilomar Conference on Signals, Systems and Computers 2009
DOI: 10.1109/acssc.2009.5469932
|View full text |Cite
|
Sign up to set email alerts
|

Rapid direct sequence spread spectrum code synchronization using a complex matched filter on an FPGA

Abstract: We present an algorithm and real time implementation for rapid code phase synchronization to direct sequence spread spectrum signals.The synchronization algorithm utilizes a complex matched filter to achieve code synchronization without sequential search over code phases, significantly reducing synchronization time. The algorithm is implemented on a Xilinx Spartan FPGA and is highly tailored to exploit the integrated signal processing resources on that device. Real time performance was demonstrated using less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On the other hand, the accrued multiaccess interference resulting from simultaneous asynchronous transmissions and consequently the system bit error performance strongly depend on signal waveform shaping as well. 14,15 Acquisition performance enhancement algorithms were also introduced for binary offset carrier signaling schemes used in GNSS. For a DS-SS receiver timing synchronization system employing initial coarse timing search followed by fine delay-locked loop (DLL) tracking, it is found that the signaling waveforms properties play an important role affecting timing acquisition capability and residual jitter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the accrued multiaccess interference resulting from simultaneous asynchronous transmissions and consequently the system bit error performance strongly depend on signal waveform shaping as well. 14,15 Acquisition performance enhancement algorithms were also introduced for binary offset carrier signaling schemes used in GNSS. For a DS-SS receiver timing synchronization system employing initial coarse timing search followed by fine delay-locked loop (DLL) tracking, it is found that the signaling waveforms properties play an important role affecting timing acquisition capability and residual jitter.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several research contributions focused on the design of fast acquisition schemes for efficient hardware implementation. 14,15 Acquisition performance enhancement algorithms were also introduced for binary offset carrier signaling schemes used in GNSS. [16][17][18] Signal design under various constraints was discussed in Landolsi 19 where full-and partial-response waveforms were proposed for the maximization of timing acquisition probability and in Giunta et al 20 where constrained optimization for noncoherent acquisition of DS-SS signals was based on generalized Q-functions.…”
Section: Introductionmentioning
confidence: 99%